Combining like terms Whole number coefficients Online Quiz

Following quiz provides Multiple Choice Questions (MCQs) related to Combining like terms Whole number coefficients. You will have to read all the given answers and click over the correct answer. If you are not sure about the answer then you can check the answer using Show Answer button. You can use Next Quiz button to check new set of questions in the quiz.

Q 1 - Simplify the following expression by combining like terms:

5a + 4b − 5c + 6a + 9b

Explanation

Step 1:

Combining like terms

5a + 4b − 5c + 6a + 9b = (5a + 6a) + (4b + 9b) – 5c

Step 2:

(5a + 6a) + (4b + 9b) – 5c

= 11a + 13b – 5c

Step 3:

So, 5a + 4b − 5c + 6a + 9b

= 11a + 13b – 5c

Q 2 - Simplify the following expression by combining like terms:

7f + 8g + 4f + 3f + 6f + 2g

Explanation

Step 1:

Combining like terms

7f + 8g + 4f + 3f + 6f + 2g

= (3f + 4f + 6f + 7f) + (8g + 2g)

Step 2:

(3f + 4f + 6f + 7f) + (8g + 2g) = 20f + 10g

Step 3:

So, 7f + 8g + 4f + 3f + 6f + 2g

= 20f + 10g

Q 3 - Simplify the following expression by combining like terms:

12x − 15y − 18x + 17y + 20x

Explanation

Step 1:

Combining like terms

12x − 15y − 18x + 17y + 20x

= (12x −18x + 20x) + (−15y + 17y)

Step 2:

(12x −18x + 20x) + (−15y + 17y) = 14x + 2y

Step 3:

So, 12x − 15y − 18x + 17y + 20x

= 14x + 2y

Q 4 - Simplify the following expression by combining like terms:

10x + 3y + 3x + 4y + 5x + 3z

Explanation

Step 1:

Combining like terms

10x + 3y + 3x + 4y + 5x + 3z

= (10x + 3x + 5x) + (3y + 4y) + 3z

Step 2:

(10x + 3x + 5x) + (3y + 4y) + 3z

= 18x + 7y + 3z

Step 3:

So, 10x + 3y + 3x + 4y + 5x + 3z

= 18x + 7y + 3z

Q 5 - Simplify the following expression by combining like terms:

9x + 7y + 4x − 11y + 10x – 8x

Explanation

Step 1:

Combining like terms

9x + 7y + 4x − 11y + 10x – 8x

= (9x + 4x +10x −8x) + (7y – 11y)

Step 2:

(9x + 4x +10x −8x) + (7y – 11y)

= 15x – 4y

Step 3:

So, 9x + 7y + 4x − 11y + 10x – 8x

= 15x – 4y

Q 6 - Simplify the following expression by combining like terms:

3x + 15y − 7x + 10y + 9z

Explanation

Step 1:

Combining like terms

3x + 15y − 7x + 10y + 9z

= (3x −7x) + (10y + 15y) + 9z

Step 2:

(3x −7x) + (10y + 15y) + 9z

= −4x + 25y + 9z

Step 3:

So, 3x + 15y − 7x + 10y + 9z

= −4x + 25y + 9z

Q 7 - Simplify the following expression by combining like terms:

8a + 7b + 2b + 3a −5c

Explanation

Step 1:

Combining like terms

8a + 7b + 2b + 3a − 5c

= (8a + 3a) + (2b + 7b) − 5c

Step 2:

(8a + 3a) + (2b + 7b) − 5c

= 11a + 9b − 5c

Step 3:

So, 8a + 7b + 2b + 3a − 5c

= 11a + 9b − 5c

Q 8 - Simplify the following expression by combining like terms:

10a + 7b + 6c + 8a + 6b + 9c

Explanation

Step 1:

Combining like terms

10a + 7b + 6c + 8a + 6b + 9c

= (10a + 8a) + (6b + 7b) + (6c + 9c)

Step 2:

(10a + 8a) + (6b + 7b) + (6c + 9c)

= 18a + 13b + 15c

Step 3:

So, 10a + 7b + 6c + 8a + 6b + 9c

= 18a + 13b + 15c

Q 9 - Simplify the following expression by combining like terms:

20x − 2xy2 + 3x − 13xy2

Explanation

Step 1:

Combining like terms

20x − 2xy2 + 3x − 13xy2

= (20x + 3x) − (2xy2 + 13xy2)

Step 2:

(20x + 3x) − (2xy2 + 13xy2)

= 23x − 15xy2

Step 3:

So, 20x − 2xy2 + 3x − 13xy2

= 23x − 15xy2

Q 10 - Simplify the following expression by combining like terms:

2x + 8y + 8x + 9y − 5y − 17z + 5z

Explanation

Step 1:

Combining like terms

2x + 8y + 8x + 9y − 5y − 17z + 5z

= (2x + 8x) + (8y + 9y −5y) + (5z − 17z)

Step 2:

(2x + 8x) + (8y + 9y − 5y) + (5z − 17z)

= 10x + 12y − 12z

Step 3:

So, 2x + 8y + 8x + 9y − 5y − 17z + 5z

= 10x + 12y − 12z

combining_like_terms_whole_number_coefficients.htm